New insights into the epidemiology of malaria relevant for disease control. - Snow, R; Marsh, K (1998)
Despite over 100 years of scientific investigation, malaria remains the leading cause of death among children living in sub-Saharan Africa. Our understanding of the epidemiology of clinical malaria has, until recently, been hampered by a paucity of empirical data from endemic settings. A striking feature of Plasmodium falciparum malaria is that, compared to infection and mild disease, severe complications and death are rare. Perhaps the single most important factor which ameliorates the risk of asymptomatic infection progressing to life-threatening pathology is the development of clinical immunity. Examination of recent epidemiological evidence suggests that the speed with which clinical immunity is acquired is dependent upon the frequency of parasite exposure from birth. Consequently, the age at which disease presentation peaks, the clinical spectrum of disease and the life-time risks of disease appear to be a function of the intensity of transmission within a given community. These observations are discussed in relation to control measures aimed at reducing P. falciparum exposure and the need to understand better the processes by which children naturally acquire clinical immunity before more rational statements can be made about their wide-spread use in Africa.